A high-power high-dielectric constant microwave garnet ferrite material and preparation method

By doping Bi3+ in garnet ferrite and jointly replacing elements such as Gd, Sn, Zr, V, etc., and adding Co2+ and Ge4+ ions to optimize the chemical ratio, the problem of difficult to take into account in the existing technology is solved, and the high power and miniaturization effect is achieved.

CN118993721BActive Publication Date: 2025-04-04SOUTH CHINA UNIV OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411471848.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-04-04
Estimated Expiration
2044-10-22

AI Technical Summary

Technical Problem

The prior art is difficult to achieve high dielectric constant, high spin wave line width and low ferromagnetic resonance line width in garnet ferrite materials at the same time, making it difficult to take into account the high power performance and miniaturization requirements of devices.

Method used

By doping a large amount of Bi3+ in the garnet ferrite, and jointly replacing elements such as Gd, Sn, Zr, V, and adding Co2+ and Ge4+ ions at the same time, the chemical ratio of the material is optimized to overcome the contradiction between the dielectric constant and the ferromagnetic resonance line width.

Benefits of technology

It achieves the balance of high dielectric constant, low ferromagnetic resonance line width and high spin wave line width, improves the high power performance and miniaturization ability of the material, and is suitable for the preparation of microwave devices such as small-sized circulators and isolators.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118993721B_ABST
    Figure CN118993721B_ABST
Patent Text Reader

Abstract

The present invention discloses a high-power high dielectric constant microwave garnet ferrite material and a preparation method thereof. The chemical formula of the garnet ferrite material is: Y 3‑x‑y‑a‑b‑2c Bi x G y Ca a+b+ 2c Sn a Zr b (CoGe) ε V c Fe 5‑a‑b‑c‑2ε‑θ O 12 , wherein 0.8≤x≤1.2, 0.01≤y≤0.5, 0.01≤c≤0.08, 0.005≤ε≤0.03, θ is the iron deficiency; the values ​​of a and b satisfy: 0≤a≤0.5, 0.15≤b≤0.5, and 0.15≤a+b≤0.5. The garnet ferrite material of the present invention has a high dielectric constant, a low ferromagnetic resonance line width and a high spin wave line width, so that the magnetic loss and power resistance characteristics of the material can be taken into account, and can be used as a high-power microwave material in small-size high-power microwave devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of microwave ferrite materials, and in particular to a high-power and high-dielectric-constant microwave garnet ferrite material and a preparation method thereof. Background Art

[0002] Garnet ferrite materials are widely used in microwave devices such as circulators and isolators because of their excellent microwave performance. With the development of microwave technology, the system is developing towards miniaturization, planarization and integration, which requires the size of devices to be smaller and smaller. The dielectric constant of ordinary garnet ferrite is usually between 12-16, which limits the miniaturization of devices. It is crucial to break through the limitation of garnet's low dielectric constant. Garnet ferrite with a high Bi content has an abnormally high dielectric constant, which can significantly reduce the size of microwave devices such as circulators and isolators to meet the needs of miniaturization. High-power microwave (HPM) refers to strong electromagnetic radiation with a frequency of 300MHz~300GHz, a pulse power of more than 100MW or an average power of more than 1MW. High-power performance is also the development trend of microwave technology, especially the miniaturization and planarization of devices, which makes the power it carries doubled, and the power resistance characteristics of materials are particularly important.

[0003] In order to obtain a high dielectric constant garnet ferrite (generally with a dielectric constant greater than or equal to 20), Bi is usually used at the dodecahedral position. 3+ Element substitution Y 3+ , but a lot of Bi 3+ A significant increase in the dielectric constant will also cause an increase in the ferromagnetic resonance linewidth ΔH, resulting in increased losses. There is a prominent contradiction between the high dielectric constant and the low ferromagnetic resonance linewidth ΔH.

[0004] The peak power capability of the device depends mainly on the high power critical field h of the material. c , a higher critical field can effectively avoid the situation where the high-power nonlinear effect of the material caused by the working environment of the device increases the loss. High-power critical field and material spin wave line width ΔH k is closely related, so increasing the spin wave line width ΔH k It is a prerequisite for increasing the peak power. In order to increase the spin wave line width ΔH of the material k Rare earth ions such as Dy, Ho, and Sm are usually used to replace the dodecahedral positions in garnet crystals, but the doping of fast-relaxing ions at the dodecahedral positions increases the spin wave line width ΔH k At the same time, the ferromagnetic resonance line width ΔH increases sharply; the spin wave line width ΔH k There is a prominent contradiction between this and the ferromagnetic resonance line width ΔH.

[0005] Therefore, how to obtain high dielectric constant and high spin wave line width ΔH k Garnet ferrite materials with low ferromagnetic resonance linewidth ΔH are problems that are difficult to solve in the existing technology. Summary of the invention

[0006] In order to overcome the above-mentioned shortcomings and deficiencies of the prior art, the object of the present invention is to provide a high-power high dielectric constant microwave garnet ferrite material. The present invention firstly dopes a relatively large amount of Bi in the garnet ferrite. 3+ By combining appropriate amounts of Gd, Sn, Zr, and V, the contradiction between high dielectric constant and low ferromagnetic resonance line width ΔH is overcome, and garnet ferrite with high dielectric constant and low ferromagnetic resonance line width ΔH is obtained. 2+ Ions and Ge 4+ Ion substitution of Fe in garnet ferrite 3+ ions, overcoming the spin wave linewidth ΔH k There is a contradiction between the ferromagnetic resonance line width ΔH and the spin wave line width ΔH. k At the same time, the ferromagnetic resonance line width ΔH is maintained at a low value, and even the ferromagnetic resonance line width ΔH is further reduced; thereby obtaining a high dielectric constant and a high spin wave line width ΔH k And garnet ferrite materials with low ferromagnetic resonance linewidth ΔH.

[0007] Another object of the present invention is to provide a method for preparing a high-power microwave garnet ferrite material, wherein the prepared high-power microwave garnet ferrite material has small and uniform grains and a uniform grain size.

[0008] The purpose of the present invention is achieved through the following technical solutions:

[0009] The present invention provides a high-power high dielectric constant microwave garnet ferrite material, the chemical formula of which is: 3-x-y-a-b-2c Bi x G y Ca a+b+2c Sn a Zr b (CoGe) ε V c Fe 5-a-b-c-2ε-θ O 12 , where 0.8≤x≤1.2, 0.01≤y≤0.5, 0.01≤c≤0.08, 0.005≤ε≤0.03, θ is the iron deficiency; the values ​​of a and b satisfy: 0≤a≤0.5, 0.15≤b≤0.5, and 0.15≤a+b≤0.5.

[0010] Preferably, in the high-power high dielectric constant microwave garnet ferrite material, 0.8≤x≤1.0, 0.01≤y≤0.3, 0.01≤c≤0.06, 0.2≤a+b≤0.4, and 0.01≤c≤0.06.

[0011] Preferably, in the high-power high dielectric constant microwave garnet ferrite material, 0.8≤x≤1.0, 0.15≤y≤0.25, a=0, 0.3≤b≤0.4, 0.015≤c≤0.025, and 0.005≤ε≤0.015.

[0012] Preferably, in the high-power high dielectric constant microwave garnet ferrite material, 0.8≤x≤1.0, 0.04≤y≤0.06, 0.10≤a≤0.25, 0.15≤b≤0.25, 0.04≤c≤0.06, and 0.01≤ε≤0.02.

[0013] The present invention also provides a method for preparing the high-power high dielectric constant microwave garnet ferrite material, comprising the following steps:

[0014] (1) Take Y2O3, Gd2O3, CaCO3, Bi2O3, SnO2, ZrO2, V2O5, Co2O3, GeO2, Fe2O3 as raw materials and weigh the raw materials according to the chemical formula;

[0015] (2) The raw materials weighed in step (1) are subjected to a first ball milling, a first drying, a first pre-calcining, a second ball milling, a second drying, a second pre-calcining, a third ball milling, a third drying and calcining, and then granulated, pressed into shape, and then sintered in air or oxygen.

[0016] Preferably, the purity of Y2O3 and Gd2O3 in step (1) is 4N; and the CaCO3, Bi2O3, SnO2, ZrO2, V2O5, Co2O3, GeO2, and Fe2O3 are analytically pure.

[0017] Preferably, in the first ball milling, the ball milling medium is distilled water or alcohol or a mixture of distilled water and alcohol; the mass ratio of material, ball: medium is 1: (2-4): (0.8-1.4), and the ball milling time is 18-36 hours;

[0018] In the second ball milling, the ball milling medium is distilled water or alcohol or a mixture of distilled water and alcohol; the mass ratio of material, ball: medium is 1: (2-4): (0.8-1.4), and the ball milling time is 18-36 hours;

[0019] In the third ball milling, the ball milling medium is distilled water or alcohol or a mixture of distilled water and alcohol; the mass ratio of material, ball: medium is 1: (2-4): (0.8-1.4), and the ball milling time is 18-36 hours.

[0020] Preferably, in the first pre-firing, the pre-firing temperature is 850-950 degrees Celsius, and the holding time is 4-10 hours; in the second pre-firing, the pre-firing temperature is 850-950 degrees Celsius, and the holding time is 4-10 hours.

[0021] Preferably, the sintering temperature is 950-1200 degrees Celsius, and the holding time is 10-20 hours.

[0022] The present invention also provides application of the high-power high-dielectric constant microwave garnet ferrite material for preparing a circulator or an isolator.

[0023] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0024] (1) The high-power high dielectric constant microwave garnet ferrite material of the present invention is firstly doped with a large amount of Bi in the garnet ferrite. 3+ By combining appropriate amounts of Gd, Sn, Zr, and V, garnet ferrite with high dielectric constant and low ferromagnetic resonance line width ΔH is obtained. 2+ Ions and Ge 4+ Ion substitution of Fe in garnet ferrite 3+ Ion, Co 2+ Ions and Ge 4+ The spin wave line width ΔH is within a specific range when the ion joint substitution amount is within a specific range. k While increasing, the ferromagnetic resonance line width ΔH is prevented from deteriorating. In a more preferred range, the ferromagnetic resonance line width ΔH is optimized at the same time.

[0025] (2) The high-power high dielectric constant microwave garnet ferrite material of the present invention overcomes the contradiction between the high dielectric constant and the low ferromagnetic resonance line width ΔH in the prior art and the spin wave line width ΔH k The contradiction between the ferromagnetic resonance line width ΔH leads to the high dielectric constant and high spin wave line width ΔH k Garnet ferrite materials with low ferromagnetic resonance linewidth ΔH are particularly suitable for preparing small-sized microwave devices such as circulators and isolators.

[0026] (3) The preparation method of the high-power and high-dielectric-constant microwave garnet ferrite material of the present invention can obtain pure-phase garnet ferrite with smaller grains and uniform grain size by adding substitution elements and adjusting the ratio between the elements, and combining the process method of the present invention, using a pressureless sintering process. While further improving the high-power performance of the microwave garnet ferrite material, it has the advantage of a simple sintering process and can be mass-produced. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is the XRD spectrum of the high-power and high-dielectric-constant microwave garnet ferrite material (ε is 0.015) according to Example 1 of the present invention.

[0028] Figure 2 This is a scanning electron microscope (SEM) photograph of the high-power and high dielectric constant microwave garnet ferrite material (ε is 0.015) according to Example 1 of the present invention.

[0029] Figure 3 This is the XRD spectrum of the high-power and high-dielectric-constant microwave garnet ferrite material (ε is 0.02) according to Example 2 of the present invention.

[0030] Figure 4 This is a scanning electron microscope (SEM) photograph of the high-power and high dielectric constant microwave garnet ferrite material (ε is 0.02) according to Example 2 of the present invention. DETAILED DESCRIPTION

[0031] The present invention will be further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto.

[0032] Example 1

[0033] In this embodiment, the chemical formula of the high-power high dielectric constant microwave garnet ferrite material is:

[0034] Y 3-x-y-a-b-2c Bi x G y Ca a+b+2c Sn a Zr b (CoGe) ε V c Fe 5-a-b-c-2ε-θ O 12 Among them, x=0.9, y=0.2, a=0, b=0.35, c=0.02, and ε is 0, 0.005, 0.01, 0.015, 0.02 and 0.03 respectively.

[0035] The preparation method of this embodiment is:

[0036] (1) Take Y2O3, Gd2O3, CaCO3, Bi2O3, SnO2, ZrO2, V2O5, Co2O3, GeO2, Fe2O3 as raw materials and weigh the raw materials according to the chemical formula;

[0037] Among them, the purity of Y2O3 and Gd2O3 is 4N, excluding the influence of impurity rare earth; the CaCO3, Bi2O3, SnO2, ZrO2, V2O5, Co2O3, GeO2, Fe2O3 can be analytically pure; Fe2O3 is dried in advance;

[0038] (2) The raw materials weighed in step (1) are subjected to the first ball milling, the first drying, the first pre-calcining, the second ball milling, the second drying, the second pre-calcining, the third ball milling, the third drying and calcining, and then granulated. After pressing into a shape, the raw materials are sintered in a muffle furnace in an air atmosphere at 1100° C. for 20 hours to obtain a sample.

[0039] Among them, in the first ball milling, the mass ratio of material: ball: medium is 1:2:1.4, the ball milling time is 18h, and the ball milling medium is alcohol.

[0040] In the second ball milling, the mass ratio of material: ball: medium was 1:2:1.2, the ball milling time was 18 h, and the ball milling medium was alcohol.

[0041] In the third ball milling, the mass ratio of material: ball: medium was 1:2:0.8, the ball milling time was 36 h, and the ball milling medium was alcohol.

[0042] In the first pre-firing, the pre-firing temperature is kept at 920℃ for 5 hours;

[0043] In the second pre-firing, the temperature is kept at 900°C for 5 hours.

[0044] The samples prepared in step (2) of this embodiment were processed by grinding to make the samples required for testing and then subjected to electromagnetic performance testing. The measurement results are shown in Table 1 below.

[0045] Table 1 Electromagnetic performance parameters of garnet material ferrite material of Example 1

[0046]

[0047] From Table 1, we can see that Co 2+ Ions and Ge 4+The addition of ions has almost no effect on the dielectric constant and dielectric loss of the garnet ferrite material of this embodiment. The Curie temperature and saturation magnetization decrease with the increase of the substitution amount ε, but because the substitution amount is small, the saturation magnetization and Curie temperature do not decrease significantly, and there is almost no effect on the application. The spin wave line width increases significantly with the increase of the substitution amount ε in the range of 0 to 0.03 of the substitution amount ε; the ferromagnetic resonance line width decreases with the increase of the substitution amount ε in the range of 0 to 0.01 of the substitution amount ε, and increases with the increase of the substitution amount ε in the range of 0.01 to 0.03 of the substitution amount ε. In the range of 0.005 to 0.03 of the substitution amount ε, the spin wave line width is greatly improved, while the ferromagnetic resonance line width is maintained at a low level. Among them, in the preferred range of 0.005 to 0.015 of the substitution amount ε, the spin wave line width ΔH k While increasing, the ferromagnetic resonance line width ΔH is prevented from deteriorating. In the more preferred range of the substitution amount ε of 0.005~0.01, the ferromagnetic resonance line width ΔH is also optimized.

[0048] The sample (ε=0.015) prepared in step (2) of this embodiment was subjected to XRD test, and the results are as follows: Figure 1 As shown in the figure, compared with the standard spectrum of pure YIG (PDF#43-0507), trace amounts of Co 2+ -Ge 4+ The co-substituted garnet ferrite is a pure garnet phase.

[0049] The sample (ε=0.015) prepared in step (2) of this embodiment was subjected to SEM test, and the results are as follows: Figure 2 As shown in the figure, it can be seen that the ferrite material has uniform grain size and a particle size of about 5um, with fewer pores and good density.

[0050] Example 2

[0051] In this embodiment, the chemical formula of the high-power high dielectric constant microwave garnet ferrite material is:

[0052] Y 3-x-y-a-b-2c Bi x G y Ca a+b+2c Sn a Zr b (CoGe) ε V c Fe 5-a-b-c-2ε-θ O 12 , where x=0.9, y=0.05, a=0.15, b=0.2, c=0.05, and ε are 0, 0.01, 0.02, and 0.03 respectively.

[0053] The preparation method of this embodiment is:

[0054] (1) Take Y2O3, Gd2O3, CaCO3, Bi2O3, SnO2, ZrO2, V2O5, Co2O3, GeO2, Fe2O3 as raw materials and weigh the raw materials according to the chemical formula;

[0055] Among them, the purity of Y2O3 and Gd2O3 is 4N, excluding the influence of rare earth impurities; the CaCO3, Bi2O3, SnO2, ZrO2, V2O5, Co2O3, GeO2, and Fe2O3 can be analytically pure; Fe2O3 is dried in advance.

[0056] (2) The raw materials weighed in step (1) were subjected to the first ball milling, the first drying, the first pre-calcining, the second ball milling, the second drying, the second pre-calcining, the third ball milling, the third drying and calcining, and then granulated. After being pressed into shape, the granulated sample was sintered at 1060° C. for 20 hours in a muffle furnace in an air atmosphere to obtain a sample.

[0057] Among them, in the first ball milling, the mass ratio of material: ball: medium is 1:3:1.4, the ball milling time is 24h; and the ball milling medium is alcohol.

[0058] In the second ball milling, the mass ratio of material: ball: medium was 1:3:1.2, the ball milling time was 24 h, and the ball milling medium was alcohol.

[0059] In the third ball milling, the mass ratio of material: ball: medium was 1:3:0.8, the ball milling time was 36 h, and the ball milling medium was alcohol.

[0060] In the first pre-sintering, the steel is pre-sintered at 900℃ for 5 hours;

[0061] In the second pre-firing, the temperature is kept at 880°C for 5 hours.

[0062] The samples prepared in step (2) of this embodiment were processed by grinding to make the samples required for testing and then subjected to electromagnetic performance testing. The measurement results are shown in Table 2 below.

[0063] Table 2 Electromagnetic performance parameters of garnet material ferrite material of Example 2

[0064]

[0065] From Table 2, we can see that Co 2+ Ions and Ge 4+The addition of ions has almost no effect on the dielectric constant and dielectric loss of the garnet ferrite material of this embodiment. The saturation magnetization and Curie temperature decrease with the increase of the substitution amount ε, but because the substitution amount is small, the Curie temperature and saturation magnetization decrease not significantly, and there is almost no effect on the application. The spin wave line width increases significantly with the increase of the substitution amount ε in the range of 0 to 0.03 of the substitution amount ε; the ferromagnetic resonance line width decreases with the increase of the substitution amount ε in the range of 0 to 0.02 of the substitution amount ε, and increases with the increase of the substitution amount ε in the range of 0.02 to 0.03 of the substitution amount ε. In the range of 0.01 to 0.03 of the substitution amount ε, the spin wave line width is greatly improved, while the ferromagnetic resonance line width is maintained at a low level. Among them, in the preferred range of 0.01 to 0.02 of the substitution amount ε, the ferromagnetic resonance line width ΔH is optimized at the same time, with the substitution amount ε of 0.02 being the best.

[0066] The sample (ε=0.02) prepared in step (2) of this embodiment was subjected to XRD test, and the results are as follows: Figure 3 As shown in the figure, compared with the standard spectrum of pure YIG (PDF#43-0507), trace amounts of Co 2+ -Ge 4+ The co-substituted garnet ferrite is a pure garnet phase.

[0067] The sample (ε=0.02) prepared in step (2) of this embodiment was subjected to SEM test, and the results are as follows: Figure 4 As shown in the figure, it can be seen that the ferrite material has uniform grain size and a particle size of about 5um, with fewer pores and good density.

[0068] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A high-power high dielectric constant microwave garnet ferrite material, characterized in that: Its chemical formula is: Y 3-x-y-a-b-2c Bi x G y Ca a+b+2c Sn a Zr b (CoGe) ε V c Fe 5-a-b-c-2ε-θ O 12 , where x=0.9, y=0.2, a=0, b=0.35, c=0.02, ε is 0.005 and 0.01 respectively; θ is the iron deficiency.

2. A high-power high dielectric constant microwave garnet ferrite material, characterized in that: Its chemical formula is: Y 3-x-y-a-b-2c Bi x G y Ca a+b+2c Sn a Zr b (CoGe) ε V c Fe 5-a-b-c-2ε-θ O 12 , where x=0.9, y=0.05, a=0.15, b=0.2, c=0.05, ε is 0.01 and 0.02 respectively; θ is the iron deficiency.

3. The method for preparing the high-power high dielectric constant microwave garnet ferrite material according to claim 1 or 2, characterized in that: The following steps are involved: (1) Take Y2O3, Gd2O3, CaCO3, Bi2O3, SnO2, ZrO2, V2O5, Co2O3, GeO2, Fe2O3 as raw materials and weigh the raw materials according to the chemical formula; (2) The raw materials weighed in step (1) are subjected to a first ball milling, a first drying, a first pre-calcining, a second ball milling, a second drying, a second pre-calcining, a third ball milling, and a third drying, and then granulated, pressed into a shape, and then sintered in air or oxygen.

4. The preparation method according to claim 3, characterized in that: In step (1), the purity of Y2O3 and Gd2O3 is 4N; the CaCO3, Bi2O3, SnO2, ZrO2, V2O5, Co2O3, GeO2 and Fe2O3 are analytically pure.

5. The preparation method according to claim 3, characterized in that: In the first ball milling, the second ball milling and the third ball milling, the ball milling medium is distilled water or alcohol or a mixture of distilled water and alcohol; the mass ratio of material, ball: medium is 1: (2-4): (0.8-1.4), and the ball milling time is 18-36 hours.

6. The preparation method according to claim 3, characterized in that: In the first pre-firing and the second pre-firing, the pre-firing temperature is 850-950 degrees Celsius and the heat preservation time is 4-10 hours.

7. The preparation method according to claim 3, characterized in that: The sintering temperature is 950-1200 degrees Celsius, and the holding time is 10-20 hours.

8. Application of the high-power high dielectric constant microwave garnet ferrite material according to claim 1 or 2, characterized in that: Used to prepare circulators or isolators.

Citation Information

Patent Citations

  • Garnet ferrite material applied to ultrahigh-power lock-type phase shifter

    CN108191423A

  • Garnet ferrite material with high dielectric constant and high saturation magnetization intensity and preparation method and application thereof

    CN111825441A

  • Garnet ferrite material as well as preparation method and application thereof

    CN112661503A